Effect of Fruit Maturity and Extraction Treatment on Germination Percentage of Langusei (Ficus minahassae (Teysm.et.Vr.) Miq)) - Irawan, Arif Irawan; Iwanuddin , Iwanuddin Iwanuddin; Jafred , Jafred Elsjoni Halawane; Fuad, Fuad Muhammad (Forestry Department, University of Muhammadiyah Makassar, 2020)
Langusei (Ficus minahassae (Teysm.et.Vr.) Miq) is one of the endemic flora of Sulawesi which existence is increasingly threatened. Attempts to maintain the existence of Ficus minahassae species by understanding the cultivation techniques of the langusei species, especially regarding the appropriate germination techniques, need to be addressed. This study aims to determine the level of fruit maturity and the appropriate extraction treatment for the germination of langusei seeds. The experimental design used in this study was a complete randomization design which is arranged in a factorial pattern. The first factor is the classification of the level of seed maturity based on fruit color categories: 1) Orange-brown fruit, 2) Orange-reddish fruit, 3) Red fruit, and 4) Red-black fruit, while the second factor is the fruit extraction treatment which consists of: 1) Extraction with dry wind treatment for 24 hours, 2) Extraction with drying treatment for 12 hours, and 3) Extraction with water treatment for 24 hours. The results showed that the fruit maturity level and the appropriate extraction treatment to produce optimal langusei seed germination were in the orange-brown and orange-reddish fruit (mature fruits prior to ripening) which was soaked in water for 24 hours.